Conferences of European bishops of the Russian Orthodox Church outside Russia under chairmanship of archbishop John (Maksimovich) in 1952 and 1954 - Aleksandr Kornilov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article examines the documentary materials of the meetings of bishops of the Russian Church Abroad, held in 1952 and 1954 under chairmanship of St. John, Archbishop of Brussels and Western Europe. The documents of the meetings were deposited in the archives of the German Diocese of the ROCOR. The issues of managing ROCOR parishes in Western European countries in the 1950-1960s still remain poorly studied, and the author provides an overview of the historiography of the problem. It is noted that the Western European Diocese included the Vicariate of Geneva and the Diocese of Preston. The competence of Archbishop John's administration also included the German diocese and the North German vicariate, the Vienna and Austrian dioceses. The author identifies such issues of church life as: the shortage of clergy, the veneration of Western saints glorified before the Great Schism of 1054, the study of the applicability of the Western rite for the conversion of non-Orthodox people from Western European countries to Orthodoxy, the organization of Orthodox congresses, youth camps, the teaching of the Law of God to the Orthodox youth. It was found that the parishes of the ROCOR had complex relations with the clergy of the Moscow Patriarchate and the Eulogian communities. At the same time, the ROCOR took advantage of the financial assistance of Lutherans and Catholics in promoting their extra-liturgical activities. The author raises the question of the need to search for new source materials for the development of the topic of diocesan management of Western European parishes of the ROCOR.